An extensional mechanism of instability and failure in the walls of open pit mines - Bridges, M.C. (Slope Stability 2013: Proceedings of the 2013 International Symposium on Slope Stability in Open Pit Mining and Civil Engineering, 2013)
Evidence from studies of instability and failures in the walls of open pit mines and cuttings indicates a predominance of an extensional mechanism, comprising toppling, ravelling and creep-subsidence. This is interpreted to arise from relief and dilation when a pit wall is excavated, removing overburden and lateral confinement of the wall. Evidence does not support sliding and shear or shallow toppling mechanisms of instability or failure.